The Impact of Branding on the Marketing Advantage and the Role of Sustainable Competitiveness as a Mediator - Hussein Falah Albadry , Zaki Muhammad Abbas , Zaid Yaseen Saud Al Dulaimi , Sami Abdullah Kadhim *, Md Fauzi Bin Ahmad (International Journal of Advanced Science and Technology, 2020)
Purpose: Iraqi electronic industry was considered one of the most efficient factories in the production among all others industries but due to war, global economic conditions and oil prices this industry has suffered a lot. The Iraqi ministry of industry is developing industrial facilities and helping to improve their industrial performance. Branding plays a major role in developing the Marketing Advantage through a Sustainable Competitiveness to increase equal opportunities and improve the efficiency. The purpose of this study is to propose a framework on the impact of branding on the marketing advantage and the role of sustainable competitiveness a mediator and empirically verify this framework.  Design/methodology/approach: The questionnaire was distributed to 204 employees of electronic industry of Bagdad Iraq, 200 were received and 4 were found high missing values so final 196 purified responses were considered for data analysis. The 7-point Likert scale was used. Data was analyzed through structural equation modeling by using Smart PLS. Findings: The result of the relationship between branding dimensions and marketing advantage was supported, except one dimension, relationship between   Reliability and Marketing Advantage r = 0.034, (r = 0.034, p<0.05) and all (10) hypotheses supported p>0.05. There is a significant mediator effect between branding and marketing advantages. Thus, factories in Iraq suffer from many problems, and after reviewing the literature, there was a great relationship between the branding and the marketing advantage and sustainable competitiveness. Research limitations/implications: This study is limit to Bagdad electric industry. Next study will be conducted for other industries and demographic. This study is cross-sectional study and time has its great impact especially after long time of war.  Practical implications: This study will help the managers of electrical industry of Iraq to understand that how to apply branding for their marketing advantages through sustainable competitiveness. Originality/value: This study has proposed a novel and unique framework and empirically verify this. This framework not only consist relationship between branding and market advantage but also have mediator effects of sustainable competitiveness.